Isokinetic strength profile of elite female handball players - Xaverova, Z.; Dirnberger, J.; Lehnert, M.; Belka, J.; Wagner, H.; Orechovska, K. (Journal of Human Kinetics, 2015)
Systematic assessment of muscle strength of the lower extremities throughout the annual training cycle in athletes is crucial from a performance perspective for the optimization of the training process, as well as a health perspective with regard to injury prevention. The main aim of the present study was to determine isokinetic muscle strength of the knee flexors and extensors in female handball players at the beginning of a preparatory period and to assess whether there were any differences between players of different performance levels. The performance level was expressed by means of membership of the Women`s Junior National Handball Team (JNT, n=8) or the Women`s National Handball Team (NT, n=9). The isokinetic peak torque during concentric and eccentric single-joint knee flexion and extension was measured at angular velocities of 60, 180, 240°/s (concentric) and 60°/s (eccentric). The Mann- Whitney test showed no significant differences in the peak torques or ipsilateral ratios between the two groups. The bilateral force deficit (BFD) for concentric extension at 240°/s was significantly higher in the JNT compared with the NT (p=0.04; d=1.02). However, the results of individual evaluation show that the BFD was more frequent in the NT in most measurements. A high BFD was evident in the eccentric mode in both groups highlighting a need for particular strengthening. With regard to low strength ratios a prevention programme should be suggested for both observed groups of professional female handball players to reduce the risk of injury.